Penerimaan Pengguna Terhadap Sistem Informasi Manajemen Rekam Medis (SIMRM) Di RSUD Tebet Jakarta Selatan Tahun 2021 - Anggi Alpiyani; Nanda Aula Rumana; Daniel Happy Putra; Laela Indawati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Rumah Sakit Umum Daerah Tebet, South Jakarta, has been using a computerized management information system for medical record services called the Hospital Information System (HIS) since 2017. The presence of the Medical Record Management Information System (SIMRM) at the Rumah Sakit Umum Daerah Tebet,  has brought many influences to services. Along with the implementation of SIMRM, it is necessary to assess whether the system is running properly and has been accepted by its users, in this case the medical record officer. The research method used The research method that the researcher uses is a quantitative descriptive method using the Technology Acceptance Model (TAM) to assess the perception of technology users as seen from 5 constructs, namely perceived ease of use, perceived usefulness. , perceptions of attitudes toward using, behavioral intention to use and actual usage by distributing questionnaires to 16 respondents consisting of 7 medical record unit officers and 9 registration unit officers. The results showed that the average user acceptance of SIMRM in South Jakarta Hospital as seen from the 5 TAM constructs was 75% received and 25% did not receive which means SIMRM was received  by the user. It is recommended for the hospital to conduct socialization and training in accordance with the needs of officers.